Structures of insect Imp-L2 suggest an alternative strategy for regulating the bioavailability of insulin-like hormones - Nikolaj Kulahin Roed (Nature Portfolio, 2018)
Insulin-like polypeptide binding proteins (IBPs) from insects can bind diverse insulin-like proteins (ILPs) including human insulin and IGFs. Here, the authors present structures of a Drosophila IBP in its free and ILP-bound forms, providing insights into the regulation of ILP bioavailability by insect IBPs.